2014
DOI: 10.1007/s00122-014-2418-4
|View full text |Cite
|
Sign up to set email alerts
|

Training set optimization under population structure in genomic selection

Abstract: Key messagePopulation structure must be evaluated before optimization of the training set population. Maximizing the phenotypic variance captured by the training set is important for optimal performance.AbstractThe optimization of the training set (TRS) in genomic selection has received much interest in both animal and plant breeding, because it is critical to the accuracy of the prediction models. In this study, five different TRS sampling algorithms, stratified sampling, mean of the coefficient of determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
354
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(403 citation statements)
references
References 58 publications
32
354
4
Order By: Relevance
“…The slopes in Reg1 were expected to be positive, as higher relationships between RP and EVA lead a higher reliability (Habier et al, 2010;Clark et al, 2012;Pszczola et al, 2012a;Rincent et al, 2012;Isidro et al, 2015;Wu et al, 2015). This was confirmed by the results of the current study as shown in Table 1.…”
Section: G à1supporting
confidence: 84%
See 3 more Smart Citations
“…The slopes in Reg1 were expected to be positive, as higher relationships between RP and EVA lead a higher reliability (Habier et al, 2010;Clark et al, 2012;Pszczola et al, 2012a;Rincent et al, 2012;Isidro et al, 2015;Wu et al, 2015). This was confirmed by the results of the current study as shown in Table 1.…”
Section: G à1supporting
confidence: 84%
“…This was confirmed by the results of the current study as shown in Table 1. In addition, low relationships in RP are desired (Pszczola et al, 2012a;Rincent et al, 2012;Isidro et al, 2015;Wu et al, 2015). Therefore, the slope in Reg2, which uses the off-diagonal elements of the inverted G, is expected to be positive (as confirmed by the results in Table 2).…”
Section: G à1mentioning
confidence: 68%
See 2 more Smart Citations
“…The genetic relatedness or population structure (Saatchi et al, 2011;Riedelsheimer et al, 2013;Wray et al, 2013) may result in overestimating the heritability of the traits (Price et al, 2010;Visscher et al, 2012;Wray et al, 2013). The population structure of the training population can be determined with greater accuracy using genome wide SNPs compared with the simple sequence repeats and SNP arrays (Isidro et al, 2015). Accuracy of estimating breeding values is important in GS.…”
Section: Genotyping Platforms Training Populations and Statistical Mmentioning
confidence: 99%